Workforce wellbeing centres and their positive role for wellbeing and presenteeism in healthcare workers during the COVID-19 pandemic: secondary analysis of COVID-Well data - Holly Blake; Helen Mancini; Emma Coyne; Joanne Cooper; Natalia Stanulewicz-Buckley (BMC, 2024)
Abstract Background Supported wellbeing centres established during the COVID-19 pandemic provided high quality rest spaces and access to peer-to-peer psychological first aid for healthcare workers (HCWs). The centres were well accessed and valued by HCWs, but their relationship with wellbeing and job-related factors is not well established. The aim of this study was to explore the relationship between wellbeing centre use, HCWs wellbeing and job-related factors (job stressfulness, job satisfaction, presenteeism, turnover intentions). Methods Secondary analysis of data from 819 HCWs from an acute hospital trust who completed an online survey in April-July 2020, as part of the COVID-Well study. Measures included the Warwick Edinburgh Mental Wellbeing Scale, and four single-item global measures of job stressfulness, job satisfaction, presenteeism and turnover intentions. ANCOVA models and regression analyses were conducted on these data. Results HCWs who had not accessed the wellbeing centres had lower wellbeing (β = 0.12, p < .001), higher job stressfulness (β = − 0.22, p < .001), lower job satisfaction (β = 0.39, p < .001), higher presenteeism (β = − 0.22, p < .001) and were of younger age (β = 0.09, p = .002). Centre use was associated with wellbeing irrespective of job stressfulness. Those reporting presenteeism and who accessed the centre (M = 3.30, SE = 0.04) had higher wellbeing than those who accessed the centre but did not report presenteeism (M = 3.06, SE = 0.04) (F(1, 791) = 18.65, p < .001, ηp 2 = 0.02). Centre use was not significantly associated with turnover intentions (B = − 0.30, p = .13; Wald = 2.26; odds = 0.74), while job stress and job satisfaction showed significant effects. Conclusions Accessing wellbeing centres was associated with higher wellbeing of HCWs, particularly for those reporting presenteeism. Therefore, the centres may have provided greatest respite and restoration for those present at work but not in optimal health. Younger workers were disproportionately affected in terms of wellbeing, and targeted support for this population is needed. Strategies to decrease presenteeism and maximise job satisfaction are urgently required. Healthcare organisations should provide rest spaces and psychological support to HCWs for the long-term, as part of a systems-wide approach to improving workforce health and wellbeing.